Ethical Perceptions of Madrasah Ibtidaiyah Teacher Candidates Toward the Utilization of Artificial Intelligence Technology in Academic Contexts - Priatmoko, Sigit; Nafi’ah, Tsaniyah; Sauny, Ananta; Aini, Febrianti (Universitas Islam Lamongan, 2025)
This study examines the ethical perceptions of Madrasah Ibtidaiyah teacher candidates regarding the use of AI in academic work, focusing on their views on academic integrity, attribution, and responsible AI practices. The research aligns these perceptions with ethical frameworks, including utilitarianism, deontology, virtue ethics, and Moral Foundation Theory (MFT). A mixed-methods Explanatory Sequential Design was employed, starting with a survey of 62 teacher candidates from UIN Malang, followed by qualitative interviews with 11 participants. The study found that AI was primarily used for assignments and coursework, with most candidates viewing AI use positively, provided clear ethical guidelines were in place. Ethical perceptions aligned with MFT’s core moral foundations—care/harm, authority/respect, and justice/fraud—as well as with utilitarian, deontological, and virtue ethics. A significant concern was the absence of formal AI policies, causing uncertainty. This study emphasizes the importance of integrating AI ethics guidelines into teacher education programs, with a focus on responsible AI use, paraphrasing techniques, and verification of AI output. Further research is needed to assess the development and impact of AI policies in teacher education, ensuring that academic integrity is maintained.